PENGEMBANGAN APLIKASI CITRA DIGITAL UNTUK MENGUBAH CITRA GREYSCALE MENJADI CITRA BERWARNA - Agus Wirahadi Putra, I Made (Universitas Pendidikan Ganesha, 2012)
This study aims at designing and developing an automatic greyscale image coloring application by implementing Global Image Matching. The input of this application is an image with bitmap (*.bmp) extension. There are two ways of coloring greyscale image, colorization and image sequences. Both of these ways have differences in the amount of the input and the output. In colorization, the input image that will be used is a greyscale image and a color image in which through this process it will be produced an output image. Meanwhile in image sequence, a greyscale image and three color images are used as the input and this will produce twelve output images. Based on the result of the study, greyscale image coloring application can be easily used in coloring the greyscale image. The software that can be used to develop the greyscale image coloring application is Delphi 2010 programming language.